2024
DOI: 10.3390/nu16081172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Elevated Dietary Copper Level on the Vascular Contractility and Oxidative Stress in Middle-Aged Rats

Klaudia Kitala-Tańska,
Katarzyna Socha,
Jerzy Juśkiewicz
et al.

Abstract: Copper (Cu), being an essential mineral, plays a crucial role in maintaining physiological homeostasis across multiple bodily systems, notably the cardiovascular system. However, an increased Cu level in the body may cause blood vessel dysfunction and oxidative stress, which is unfavorable for the cardiovascular system. Middle-aged (7–8 months old) male Wistar rats (n/group = 12) received a diet supplemented with 6.45 mg Cu/kg (100% of the recommended daily dietary quantity of copper) for 8 weeks (Group A). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
2
4
1
Order By: Relevance
“…In addition, there were no differences in the weights of the brain, heart, kidney, liver, or spleen. Previous studies support the data presented in this article [11]. Consistent with our research, Filetti et al (2023) reported that there were no significant differences in weight between the control group and the groups that were administered different amounts of copper [17].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations

Copper Supplementation in Young Wistar Rats

Kitala–Tańska,
Hanć,
Juśkiewicz
et al. 2024
Preprint
“…In addition, there were no differences in the weights of the brain, heart, kidney, liver, or spleen. Previous studies support the data presented in this article [11]. Consistent with our research, Filetti et al (2023) reported that there were no significant differences in weight between the control group and the groups that were administered different amounts of copper [17].…”
Section: Discussionsupporting
confidence: 92%
“…Compared with that in the control group, the vasodilatory response to acetylcholine in the experimental group tended to potentiate vasodilation. It is worth mentioning to the increase in vasodilation in aged rats that was previously observed [11]. Both selective COX-2 inhibition and nonselective COX inhibition (simultaneous COX-1 and COX-2 inhibition) attenuated the vasodilator net effect of prostanoids on acetylcholine-induced vascular relaxation, indicating the decreased participation of vasodilator prostanoids derived from COX-2 in vascular tone regulation.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations

Copper Supplementation in Young Wistar Rats

Kitala–Tańska,
Hanć,
Juśkiewicz
et al. 2024
Preprint